1997
DOI: 10.1023/a:1024574915201
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Seventy-three men and 72 women made lexical decisions to target words that followed sentences constructed so that the last word was a sexual double-entendre. Prime target relatedness, erotic versus nonerotic target, stimulus onset asynchrony, and participant's gender were varied in a between-subjects design. A second analysis that substituted sentence context for prime target relationship also was conducted. Data were collected on the emotionality and social acceptability of priming sentences and target words.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Such an effect is known as Sexual Content-Induced Delay. This concept was introduced by Geer and Bellard (1996) and Geer and Melton (1997) and supports the proposed controlled pathway of processing sexual stimuli in a variety of experiments (e.g., Spiering, Everaerd, & Elzinga, 2002). …”
Section: Introductionsupporting
confidence: 54%
“…Such an effect is known as Sexual Content-Induced Delay. This concept was introduced by Geer and Bellard (1996) and Geer and Melton (1997) and supports the proposed controlled pathway of processing sexual stimuli in a variety of experiments (e.g., Spiering, Everaerd, & Elzinga, 2002). …”
Section: Introductionsupporting
confidence: 54%
“…This technique has also been used in studies that examine sex-related cognitive structures (Geer and Bellard 1996; Geer and Melton 1997; Spiering et al 2002). In a typical lexical decision task, participants are presented with a mixture of words and nonwords.…”
Section: Methodsmentioning
confidence: 99%
“…and 16 neutral words (e.g., door, bank, etc.) frequently used in past research on sexual priming (Geer and Bellard 1996; Geer and Melton 1997; Spiering et al 2002) were selected to be the lexical decision stimuli. These words are frequently used in colloquial English and have similar number of letters and syllables.…”
Section: Methodsmentioning
confidence: 99%
“…These measures work on the premise that preferred sexual information is processed differently from non-sexual and nonpreferred information (Geer & Bellard, 1996;Geer & Fuhr, 1976;Geer & Melton, 1997;Janssen, Everaerd, Spiering, & Janssen, 2000;Spiering, Everaerd, & Janssen, 2003); by measuring differences in processing we may obtain an insight into the observer's sexual motivation and interest. Several studies have shown that both explicit, consciously processed sexual stimuli (Geer & Bellard, 1996;Geer, Judice, & Jackson, 1994;Geer & McGlone, 1990) and implicit non-consciously processed sexual stimuli (Spiering et al, 2003;Spiering, Everaerd, Karsdorp, Both, & Brauer, 2006) have an interfering effect on information processing, which requires additional processing time and exerts attentional capture.…”
Section: Introductionmentioning
confidence: 99%